Analisis Dampak Ketimpangan Gender terhadap Partisipasi Perempuan di Dunia Kerja - Nagita Rahma Sari; Ade Gunawan; Ferida Rahmawati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to analyze the impact of gender inequality on women's participation in the workforce, focusing on patriarchal cultural factors, corporate policies, and social norms. The research method employed is a literature study, collecting and analyzing data from journals, books, and reports related to gender and employment issues. The results indicate that gender inequality remains a significant barrier to women's participation in various job sectors, particularly in terms of promotion opportunities, unequal pay, and the double burden of domestic and professional work. The discussion elaborates on how gender stereotypes and patriarchal social structures reinforce this injustice. The conclusion emphasizes the need for inclusive policy interventions, gender equality education, and the role of the younger generation in driving change. Proposed recommendations include strengthening anti-discrimination regulations and gender awareness campaigns in the workplace.